Espaço de fé e relações de poder: o recolhimento feminino de Santa Clara de Sorocaba (1800-1850) - Garcia, Bruna De Oliveira [UNIFESP] (2020)
Since the conquest and beginning of colonization of America, the Portuguese Crown has given preference to the establishment of male religious orders. The first convent of a female order was not allowed until 1677, in Bahia, the Convent of Desterro, belonging to the Conceptionist Order. Despite the difficulties imposed by the Crown, feminine institutions were founded in the captaincies of Portuguese America. Some obtained royal authorization, others had statutes and functioned even without such authorization. These institutions, which already existed in Portugal, with other uses, helped to fill the lack of convents in Brazil and to develop the female religious life, even late. Thus the debate on colonial and imperial women also needs to be analyzed from the point of view of the women who chosSince the conquest and beginning of colonization of America, the Portuguese Crown has given preference to the establishment of male religious orders. The first convent of a female order was not allowed until 1677, in Bahia, the Convent of Desterro, belonging to the Conceptionist Order. Despite the difficulties imposed by the Crown, feminine institutions were founded in the captaincies of Portuguese America. Some obtained royal authorization, others had statutes and functioned even without such authorization. These institutions, which already existed in Portugal, with other uses, helped to fill the lack of convents in Brazil and to develop the female religious life, even late. Thus the debate on colonial and imperial women also needs to be analyzed from the point of view of the women who chose or received the imposition their religious status, since for that society only two ways were intended for women: marriage or religion. The Santa Clara de Sorocaba Convent fits into these issues, founded by women in a village relatively remote from center political power, at a time when Brazil was undergoing major changes such as the arrival of the Royal Family and then Proclamation of Independence. The documentation consulted allows us to analyze and understand the complexity of women’s religious life and how women’s religious institutions often had other uses within the same society.e or received the imposition their religious status, since for that society only two ways were intended for women: marriage or religion. The Santa Clara de Sorocaba Convent fits into these issues, founded by women in a village relatively remote from center political power, at a time when Brazil was undergoing major changes such as the arrival of the Royal Family and then Proclamation of Independence. The documentation consulted allows us to analyze and understand the complexity of women’s religious life and how women’s religious institutions often had other uses within the same society.